Propagation of preexisting dentinal microcracks after root canal preparation using rotary, reciprocating, and adaptive instruments: An ex vivo microcomputed tomographic analysis - Arunima Aggarwal; Ruchika Roongta Nawal; Sudha Yadav; Sangeeta Talwar; Sriram Kunnoth; Puneet Mahajan (Wolters Kluwer Medknow Publications, 2024)
Aim: To evaluate the propagation of preexisting dentinal microcracks after instrumentation with ProTaper Universal (PTU), ProTaper Gold (PTG), Twisted File Adaptive (TFA), and Reciproc Blue (RB) instruments by micro-CT imaging. Methods: The mesial roots of 60 mature human mandibular molars were cut out approximately 10 mm from the apex. The roots were then divided randomly into four groups (n = 15) based on file system used: PTU, PTG, TFA, and RB. Before and after canal shaping, roots were scanned with micro-CT. The preinstrumentation cross-sectional slices were examined to ascertain the presence of preexisting dentinal microcracks in apical 10 mm of radicular dentine. Postinstrumentation, the extension of preexisting dentinal microcracks was assessed and compared with corresponding preinstrumentation image to determine the grade of propagation. Postinstrumentation, the propagation of preexisting dentinal microcracks were categorized into three grades: nonpropagated dentinal microcracks (Grade 1), incomplete propagation (Grade 2), and complete propagation (Grade 3). Results: The PTU system showed a significantly higher propagation of preexisting dentinal microcracks compared to PTG, TFA, and RB system (P ≤ 0.05). All the instrumentation systems showed propagation of preexisting dentinal microcracks into Grade 2 cracks. Grade 3 propagation was seen in PTU, PTG, and RB systems. The number of Grade 2 dentinal microcracks were significantly higher than Grade 1 dentinal microcracks for the PTU system (P ≤ 0.05). Conclusion: Root canal instrumentation promotes propagation of preexisting dentinal microcracks. As compared to conventional nickel-titanium file systems, reciprocating and thermally treated file systems may less likely result in propagation of dentinal microcracks.